2018
DOI: 10.21315/mjms2018.25.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ Attitude and Barriers of Evidence Based Practice in Maternity Care

Abstract: Objectives: Midwives have a crucial role in providing optimal care for pregnant women. One of the most important policies for quality improvement in maternity care is implementation of evidence-based practice. However, the application of evidence-based practice within the maternity health care setting faces many challenges. The purpose of this study was to describe Iranian midwives' attitude and perceived barriers of evidence based practice in maternity care.Methods: In this descriptive, cross-sectional study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 35 publications
5
27
0
Order By: Relevance
“…A total of eight studies found that nurses' attitudes and experience as barriers to implementing EBP [10][11][12][13][14][15][16]19].…”
Section: Nurses Personal Attitude and Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…A total of eight studies found that nurses' attitudes and experience as barriers to implementing EBP [10][11][12][13][14][15][16]19].…”
Section: Nurses Personal Attitude and Experiencementioning
confidence: 99%
“…Similarly, 59% of nurses showed resistance to change from traditional and ritualistic practices to EBP [16]. While in a quantitative cross-sectional study aimed to describe the attitude toward the application of EBP among midwives in maternity care, the results showed the highest mean scores (4.18 ± 0.53) it improves patient health care outcomes [19].…”
Section: Nurses Personal Attitude and Experiencementioning
confidence: 99%
See 1 more Smart Citation
“… 21 Second, severe provider shortages in low-income countries means that providers often have very large patient loads and work under intense time pressures, which may pose a barrier to taking the time to explore and review evidence in the course of practice. 21 , 30 , 31 , 32 , 33 In addition, because health care providers often work in teams, lack of supportive leadership or a conducive workplace culture might pose a barrier to changing practice. 21 Finally, as in high-income settings, patients may demand services that conflict with current evidence and providers may also have negative attitudes toward EBP, seeing it as reducing their autonomy and limiting their clinical choices.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is an established body of evidence on the barriers and facilitators of EBP in healthcare, there remains limited knowledge of the factors that help or hinder midwives' efforts to implement new evidence-based practices in clinical areas (Azmoude, Aradmehr, & Dehghani, 2018). Further, little is known about midwives' use of implementation tools to facilitate the process (Bayes, Fenwick, & Jennings, 2016).…”
Section: Introductionmentioning
confidence: 99%